2011
DOI: 10.1093/rheumatology/ker317
|View full text |Cite
|
Sign up to set email alerts
|

Tension at the borders: perceptions of role overload, conflict, strain and facilitation in work, family and health roles among employed individuals with arthritis

Abstract: Objective. To examine inter-relationships among arthritis (A), work (W) and personal life (P) roles and their reciprocal influences, especially experiences of role balance/imbalance among individuals with inflammatory arthritis (IA) and OA.Methods. Eight focus groups were conducted with 24 women and 16 men (aged 29–72 years). A purposive sample was recruited from community advertising. Eligibility included current employment or having been employed within the previous year. Participants were asked about ways a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

6
53
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(59 citation statements)
references
References 36 publications
6
53
0
Order By: Relevance
“…Studies suggest that, despite improvements in treatment for rheumatic diseases, many individuals continue to report difficulties working, have elevated absenteeism rates, and report reduced productivity (1)(2)(3)(4). In addition to the physical symptoms of the disease creating difficulties for people in remaining employed, factors like job stress, symptom unpredictability, disruptions to work because of time needed for treatment, and employment factors like a lack of job control and absence of workplace support can create barriers to working (5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20).…”
Section: Introductionmentioning
confidence: 99%
“…Studies suggest that, despite improvements in treatment for rheumatic diseases, many individuals continue to report difficulties working, have elevated absenteeism rates, and report reduced productivity (1)(2)(3)(4). In addition to the physical symptoms of the disease creating difficulties for people in remaining employed, factors like job stress, symptom unpredictability, disruptions to work because of time needed for treatment, and employment factors like a lack of job control and absence of workplace support can create barriers to working (5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20).…”
Section: Introductionmentioning
confidence: 99%
“…However, the actual sense in which those terms are used is unclear and indistinct (Coverman, 1989). Previous studies that have examined balance in relation to those terms do not always define them clearly or distinguish between them (e.g., Gignac et al, 2012;Marks & MacDermid, 1996). While the studies attempted to advance knowledge on balance, the absence of a shared understanding of those terms inhibited their capacity to further refine the conceptualization of balance.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to the potentially negative impact of arthritis on work, a small number of studies have examined whether individuals perceive that their job or their personal life affects their health or management of their disease [35, 38, 42]. For example, a qualitative study of individuals with inflammatory arthritis (e.g., rheumatoid arthritis) and osteoarthritis found that many individuals reported both negative and positive aspects of working with arthritis.…”
Section: Introductionmentioning
confidence: 99%